Directional overcurrent and earth-fault protections for a biomass microgrid system in Malaysia - Bakar, Ab Halim Abu; Ooi, B.J.; Tan, Chia Kwang; Illias, Hazlee Azil; Mokhlis, Hazlie (Elsevier, 2014)
Over-current protection is principally intended to counteract excessive current in power systems. In distribution systems in Malaysia, non-directional over-current protection is adopted because of the radial nature of the power system used. Relay typically used in distribution network are designed to cater for current flow in one direction, i.e., from transmission network to load. However, with the forecasted increase in generation from renewable sources, it is important that adequate codes are in place with regards to their integration to sub-transmission/distribution network. Distribution network dynamically changes from “passive” to “active” network. With distributed generation connected to distribution network, power flows bi-directionally. Hence, directional over-current protection is adopted along the line between the transmission grid and the distributed generation. The bi-directional flow of power also complicates the earth fault protection. This is due to the presence of the distributed generation that will cause the line near the delta side of the transformer to be still energized after the operation of earth fault relay during single-phase-to-ground-fault. This paper investigates the directional over-current and earth fault protections used to protect the microgrid (biomass generator) in Malaysia. In this study, under-voltage relays are adopted at the delta side of the transformer to fully clear the single-line-to-ground fault, which cannot be cleared by earth fault relay. Three-phase-balanced fault and single-line-to-ground-fault at all possible locations in the network have been simulated. Simulation shows good coordination and discrimination between over-current relays.